Analysis of Lampung Province's Trade System and Opportunities for Upgrading in Global Value Chains (2014–2024) - Suharyadi, Irsyaad; Simon Sumanjoyo Hutagalung; Rara Gusnita Putri (Lampung Center for Global Studies (LCGS), 2025)
This study takes a close look at Lampung Province in Indonesia, focusing on its trade structure and the exciting growth potential within global value chains (GVCs). Using clear, accessible data from Statistik Perdagangan Luar Negeri Provinsi Lampung 2024, published by BPS Lampung, this report highlights Lampung’s export and import trends from 2014 to 2024. The report identifies key commodities and trading partners, and explores opportunities to upgrade functionality, markets, and social impact. The analysis shows that Lampung currently relies heavily on agro-based exports—mainly vegetable and animal oils, food products, and mineral fuels—and primarily depends on Asian markets, with some encouraging growth in exports to Europe and the Americas in 2024 (BPS Lampung, 2025). Drawing on Global Value Chain theory (Gereffi, 2018), the study proposes a framework to understand how Lampung can move from supplying raw materials to engaging in higher-value activities such as processing, branding, and market access through certification. The findings reveal that, even though export values rose and a surplus was achieved in 2024, manufacturing still accounts for only a small share of total exports, limiting opportunities for functional upgrading. While there has been some progress in diversifying markets toward Europe and North America, exports remain relatively concentrated in a few key regions. The paper offers practical policy recommendations, such as strengthening provincial economic diplomacy, supporting agro-processing industries, implementing certification and traceability systems, and fostering stakeholder collaboration to promote inclusive social upgrading for smallholders and MSMEs. Overall, this research provides valuable insights into subnational GVC development and points to actionable pathways for regional trade growth.